Estrategias De Formación Para Incrementar El Uso De Resultados De Evaluaciones En El Sector Educativo Mexicano - Martín De Los Heros Rondenil (European Scientific Journal, ESJ, 2017)
It is analysis the strategy of training to Principals of Basic Education Schools in Mexico City, was materialized with the "Educational Management Course" in the blended learning method. The training context is part of the National Educational Evaluation Policy (PNEE), which is currently being implemented in Mexico. It seeks to respond to the concern of educational authorities' about the little use of school evaluation results. This situation led us to ask questions What factors potentiate or limit the use of evaluation? These guided the design of training activities. Considering use of evaluation as "implementation of evaluation processes, products or findings to produce an effect" (Christie, 2007: 8) and considering the categories of use of evaluation results: instrumental, conceptual and symbolic (Johnson, 2009 ), in a context of adult education and ICT training; practical activities were designed and implemented to strengthen the information management and information analysis through workshops, using excel, teamwork, gathering and systematizing information, developing indicators and writing the arguments of the school curricula. The evaluation of the perception of School Principals (175 cases) and the assessment of the School Improvement Routes by the tutors (5 cases) showed greater use of evaluation, educational information, management and context results, in the School Improvement Route